Predictions of Muslim Middle Class Consumer Behavior in Indonesia in 2025: English - Azis, Hadi; Irwan, Risky (Sekolah Pascasarjana Universitas Ibn Khaldun Bogor, 2024)
This research intended to predict the behavior of Muslim middle class consumers in Indonesia in 2025. The rapid growth of the Muslim middle class in Indonesia creates great opportunities for various sectors, especially the halal industry, fashion, and tourism. To understand these changes in consumption patterns, research methods using a quantitative approach with survey methods. Data was collected through an online questionnaire distributed to 100 respondents representing the Muslim middle class in Indonesia. Apart from that, in-depth interviews were conducted with 20 sources from economic experts, sociologists, celebrities, public figures and industry players. Data analysis was carried out using the multiple regression method to identify the main factors that influence consumption behavior, such as income, preference for halal products, and use of digital technology. Results and Discussion research shows that by 2025, middle class Muslim consumers in Indonesia are likely to increasingly prioritize products that comply with sharia principles, such as halal products and ethically based services. In addition, the trend of online shopping and the use of digital technology in purchasing decisions is predicted to continue to increase, along with increasing digital literacy among the public. Other significant influencing factors include awareness of sustainability and healthy lifestyles. This research also found that the role of social media is very important in influencing the preferences of middle class Muslim consumers, especially in terms of product information and customer reviews. Thus, the results of this research provide strategic insight for industry players to develop products and services that suit the needs and values ​​of Muslim consumers. It is also hoped that this research can contribute to the literature on consumer behavior in Muslim markets and become the basis for further studies in understanding consumption dynamics in Indonesia